Review on Iris Based Security System Using Edge Detection Mechanism - *Pooja1; Kumar, Mahesh (IJRDO -Journal of Computer Science Engineering, 2017)
Iris recognition is the method of biometric to be identify it’s use mathematical recognition techniques on video images of one or both of irises of an individual eye, whose difficult random patterns are unique, stable, & can be seen from some distance. Digital templates encoded from these patterns by mathematical & statistical algorithms allow identification of an individual or someone pretending to be that individual. Databases of enrolled templates are searched by matcher engines at speeds measured in millions of templates per second per (single-core) CPU, & within remarkably low false match rates.